Dicrostonyx groenlandicus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Dicrostonyx groenlandicus (Traill 1823) [Dicrostonyx] groenlandicus (Traill 1823), in: Scoresby, J. Voy. to Northern Whale-Fishery.: 416. Type Locality: Greenland, Jamesons Land. Vernacular Names: Nearctic Collared Lemming. Synonyms: Dicrostonyx alascensis Stone 1900; Dicrostonyx clarus Handley 1953; Dicrostonyx kilangmiutak Anderson and Rand 1945; Dicrostonyx lentus Handley 1953; Dicrostonyx rubricatus (Richardson 1889). Distribution: N Greenland and Queen Elizabeth Isls, islands in the District of Franklin, and Southampton Isl; N North America above treeline, from NE District of Keewatin, Canada, to N Alaska, USA. Conservation: IUCN – Lower Risk (lc) as D. groenlandicus , D. kilangmiutak , and D. rubricatus . Discussion: In their broad specific concept, Jarrell and Fredga (1993) viewed all North American taxa, except D. hudsonius , as junior synonyms, including the insular forms exsul and vinogradovi . Morphological, distributional, breeding, chromosomal, and-or molecular evidence, albeit uneven and incomplete, persuades us to maintain D. nelsoni , D. nunatakensis , D. richardsoni , D. unalascensis , and D. vinogradovi as distinct (see those accounts). Standard and banded chromosomal comparisons reported by Borowik and Engstrom (1993), who supported the synonymy of clarus and lentus . Engstrom et al. (1993) reported kilangmiutak (2n = 47-50) as karyotypically separable from D. groenlandicus (2n = 38-44), calling them "cytospecies," but found the two to be only marginally differentiated in mitochrondrial DNA sequences; samples drawn from the range of kilangmiutak are morphometrically (Eger, 1995) and genetically (Ehrich et al., 2000) unremarkable in comparisons with D. groenlandicus proper. The form rubricatus (Beringian distribution) shares a distinctive XY-autosomal fusion pattern with D. groenlandicus (Pearyland distribution), different from that found in D. richardsoni (Borowik and Engstrom, 1993); levels of differentiation in cranial form (Eger, 1995) and nucleotide sequences (Ehrich et al., 2000) provide ...